Interspeech 2019 2019
DOI: 10.21437/interspeech.2019-2661
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Evaluation of ASR Adaptation in a Lecture Context: Application to the PASTEL Corpus

Abstract: Lectures are usually known to be highly specialised in that they deal with multiple and domain specific topics. This context is challenging for Automatic Speech Recognition (ASR) systems since they are sensitive to topic variability. Language Model (LM) adaptation is a commonly used technique to address the mismatch problem between training and test data. In this paper, we are interested in a qualitative analysis in order to relevantly compare the accuracy of the LM adaptation. While word error rate is the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A further study [4] also benchmarked three commercial ASR systems, but they reported results using three metrics: WER, Hper and Rper. A qualitative analysis [10] on ASR systems was performed aiming to evaluate the accuracy of the Language Model adaptation; in order to do so, the WER metric was applied only to relevant words.…”
Section: Related Workmentioning
confidence: 99%
“…A further study [4] also benchmarked three commercial ASR systems, but they reported results using three metrics: WER, Hper and Rper. A qualitative analysis [10] on ASR systems was performed aiming to evaluate the accuracy of the Language Model adaptation; in order to do so, the WER metric was applied only to relevant words.…”
Section: Related Workmentioning
confidence: 99%
“…Other approaches explore the adaptation of the language model used by the speech recognition system. To accurately estimate the impact of language model adaptation, Mdhaffar et al (2019) first perform a qualitative analysis and then conduct experiments on a dataset in French, showing that language model adaptation reduces the WER of speech recognition significantly. Raju et al (2019) incorporate a language model into a speech recognition system and train it on heterogenous corpora so that personalized bias is reduced.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, these issues have been observed in the field of machine translation. As a result, new metrics and data sets have been produced from multiple shared tasks [26,25,9,8]. Semantic-based metrics, such as BERTScore [34], have then been shown to be effective in evaluating the quality of machine-generated translations.…”
Section: Introductionmentioning
confidence: 99%